2022
DOI: 10.1038/s41598-022-22806-9
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor function is enhanced by Interleukin-10 in human epileptogenic gangliogliomas and its effect is counteracted by Interleukin-1β

Abstract: Gangliogliomas (GGs) are low-grade brain tumours that cause intractable focal epilepsy in children and adults. In GG, as in epileptogenic focal malformations (i.e., tuberous sclerosis complex, TSC), there is evidence of sustained neuroinflammation with involvement of the pro-inflammatory cytokine IL-1β. On the other hand, anti-inflammatory mediators are less studied but bear relevance for understanding seizure mechanisms. Therefore, we investigated the effect of the key anti-inflammatory cytokine IL-10 on GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…While short-term exposure of neurons to IL-1β leads to a reduction of voltage-gated sodium currents, longer exposure (hours or days) results in a marked increase and can cause hyperexcitability [ 77 ]. The same, time-dependent effects of IL-1β are observed on GABA-A receptor mediated currents in ganglioglioma [ 78 ]. It also has been shown that IL-1β enhances expression of NMDA receptor subtype 2B leading to an increased Ca 2+ influx and hyperexcitability.…”
Section: Aetiology and Pathophysiology Of Autoimmune-mediated Seizure...mentioning
confidence: 76%
“…While short-term exposure of neurons to IL-1β leads to a reduction of voltage-gated sodium currents, longer exposure (hours or days) results in a marked increase and can cause hyperexcitability [ 77 ]. The same, time-dependent effects of IL-1β are observed on GABA-A receptor mediated currents in ganglioglioma [ 78 ]. It also has been shown that IL-1β enhances expression of NMDA receptor subtype 2B leading to an increased Ca 2+ influx and hyperexcitability.…”
Section: Aetiology and Pathophysiology Of Autoimmune-mediated Seizure...mentioning
confidence: 76%
“…Notably, IL-1β decreases GABA currents’ amplitude and impedes the efficacy of IL-10. [50] Focal epilepsy is believed to elevate IL-10 as a possible safeguarding mechanism in the brain that mitigates inflammatory harm. It is noted that IL-10 secretion is subject to seizure frequency and depletes with the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of this paper, prevention of NKCC1/KCC2-mediated changes in chloride conductance would diminish the loss of GABAergic inhibition, although an alternative explanation is that protective effects of anti-inflammatory cytokines contribute to the sparing of GABAergic inhibition in the face of neuroinflammatory insults. 8 Like other potential mechanisms, these hypotheses need to be evaluated more firmly in order to understand the causative relationship of inhibition (post-synaptic Cl − regulatory and/or presynaptic interneuronal GABA release mechanisms 9 ) in neuroinflammation and hyperexcitability/seizures. Curiously, BDNF and its inhibition (as discussed earlier) may be an important mechanism of reducing the impact of inflammation on chloride cotransporters.…”
Section: Commentarymentioning
confidence: 99%